Examining the Cause for Companies to Embrace Sustainability Practices - Rahmani, Parwana; Fatima Samimi; Yusra Ansari (Business and Human Rights Law & Policy, 2026)
Sustainability is a vital issue that significantly impacts human survival, particularly because it is fundamentally related to resource utilization, lifestyle choices, and human beings’ obligations concerning future generations. While, when it comes to the corporate sustainability, it refers to some practices which business operations consider such as social responsibility, environmental preservation, and adherence to ethical management standards. Contemporary literature defines sustainability as complete when a company's engagement in sustainable development is not only beneficial to society but also economically and financially viable for the company, thereby ensuring its long-term viability. Focusing on sustainability can directly enhance company profitability through improving reputation and brand equity. Additionally, it attracts customer trust and willingness to pay, while increasing employee productivity and retention. These factors can ultimately foster innovation and drive new developments within the organization. This article examines whether companies that embrace sustainable business practices, particularly those that focus on protection of human rights and minimize environmental harm, are more likely to achieve profitability? By analysing global trends and real-world examples, this paper demonstrates how sustainability enhances brand credibility, reduces operational and legal risks, increases consumer trust, and attracts greater investor attention. The study offers a comprehensive explanation of the economic rationale underlying sustainable behaviour and its transformative impact on corporate performance.